Ginsenoside-Rb1-Mediated Anti-angiogenesis via Regulating PEDF and miR-33a through the Activation of PPAR-γ Pathway - Lu, Huixia; Zhou, Xunian; Kwok, Hoi-Hin; Dong, Mei; Liu, Zhaoqiang; Poon, Po-Ying; Luan, Xiaorong; Ngok-Shun Wong, Ricky (Frontiers in Pharmacology, 2017)
Angiogenesis is the formation of new blood vessels from the existing vasculature, which is involved in multiple biological processes, including atherosclerosis, ischemic heart disease, and cancer. Ginsenoside-Rb1 (Rb1), the most abundant ginsenoside isolated form Panax ginseng, has been identified as a promising anti-angiogenic agent via the up-regulation of PEDF. However, the underlying molecular mechanisms still remains unknown. In the present study, human umbilical vein endothelial cells (HUVECs) were selected to perform in vitro assays. Rb1 (0-20 nM) treatment induced pigment epithelial-derived factor (PEDF) protein expression in concentration and time-dependent manners. Interestingly, it was also demonstrated that the exposure of Rb1 (10 nM) could increase PEDF protein expression without any alteration on mRNA level, suggesting the involvement of posttranscriptional regulation. Furthermore, bioinformatics predictions indicated the regulation of miR-33a on PEDF mRNA 3’-UTR, which was further confirmed by luciferase reporter gene assay and real-time PCR. Over-expression of pre-miR-33a was found to regress partly Rb1-mediated PEDF increment and anti-angiogenic effect in HUVECs. Additionally, Rb1-reduced miR-33a and increased PEDF expression was prevented by pre-incubation with peroxisome proliferator-activated receptor-γ (PPAR-γ) antagonist (GW9662) or transfection with PPAR-γ siRNA in HUVECs. Taken together, our findings demonstrated that Rb1 exerted anti-angiogenic effects through PPAR-γ signaling pathway via modulating miR-33a and PEDF expressions. Thus, Rb1 could be developed as promising agent in the treatment of angiogenesis-related diseases, such as cancer, cardiovascular disease, or ocular disorders.